ChemInform Abstract: Copper‐Catalyzed Carbochlorination or Carbobromination via Radical Cyclization of Aryl Amines. Issue 29 (June 2016) - Ouyang, Jianing; Su, Xiaolong; Chen, Yu; Yuan, Yaofeng; Li, Yi
Abstract: The new and efficient copper‐catalyzed intramolecular carbochlorination employs aryl amines as starting materials and aqueous HCl, providing a facile access to relevant 3‐chloromethyl‐2, 3‐dihydrobenzofuran derivatives.